(untitled) (Bioscience Journal, 2020)
Studies on the adaptability and stability are fundamental for plant breeding as they are an alternative to reduce the effects of genotypes x environments interaction (GxE). Moreover, they help identify cultivars with predictable behavior, which are responsive to environmental improvements, subsidizing cultivar recommendation. This study aimed to investigate the genotypes x environments interaction in cotton genotypes grown in the Brazilian Cerrado and identify genotypes for favorable and unfavorable environments. During the 2013/2014 and 2014/2015 seasons, 19 competition trials were carried out with cotton in a randomized block design, with 12 treatments, and four replications. The traits cotton seed yield, fiber percentage, fiber length, and fiber strength were evaluated. Results revealed significant GxE interaction for all the fiber traits evaluated. Genotype BRS 369 RF revealed general adaptability and high predictability for the fiber traits evaluated.